Leaders' Social and Disability Justice Drive to Cultivate Inclusive Schooling - Chelsea P. Tracy-Bronson (MDPI AG, 2024)
The purpose of this article is to understand administrators' personal beliefs and experiences related to inclusive education and social justice that are critical to their commitment, the leadership provided, and types of special education services that prevail in their districts. This study is embedded within a conceptual framework centered on inclusive education, and existing theoretical framings of leadership for social justice and disability studies in education. Further, it contributes to the conversation in a recent call to reimagine educational approaches in the United States that challenge systems, focus on racial and disability justice, and serve the public good. A qualitative research methodology with in-depth interviewing as the data collection method was used to understand the lived experiences and practices of seven district-level special education leaders. It specifically looks at the leaders' drive to carry out social justice work and their overall value-based mission of socially just, equity-oriented inclusive education at the district level. It provides a research study on (1) how leaders come to carry out social justice and disability justice work in schools, (2) poignant career events that shape their justice work, and (3) their intentions to prepare under-represented and traditionally marginalized students to engage in society. The overall premise is that since district-level leaders are vital in shaping public schooling spaces, understanding their social and disability justice grounding is critical to disrupt marginalizing practices in PreK-12.